MAIN PRINCIPLES OF TREATMENT OF GENITAL CHLAMYDIOSES AND MYCOPLASMOSES AMONG GIRLS - O.I. Nemchenko; E.V. Uvarova (Педиатрическая фармакология)
The article deals with the recommendations based on modern literature and own experience in treatment of girls, suffering from inflammatory genital diseases of chlamydia and mycoplasmal etiology. The authors examined the prescription principles of etiological, pathogenetic and symptomatic therapy, determination of terms for the therapy, criteria of chlamydiosis and genital mycoplasmosis cure, as well as backset prevention, reinfection and complications.Key words: chlamydiosis, genital mycoplasmoses, children, teenagers, treatment.